2012
DOI: 10.15407/spqeo15.02.139
|View full text |Cite
|
Sign up to set email alerts
|

Current transport mechanisms in metal – high-k dielectric – silicon structures

Abstract: Abstract. The mechanism of current transport in several high k  -dielectric, including rare earth metal oxides (Gd 2 O 3 , Nd 2 O 3 ), ternary compounds (LaLuO 3 ) and rare earth metal silicate (LaSiO x ) thin films on silicon was studied using current-voltage ( V I  ) and conductance-frequency (   G  ) measurements at temperatures 100-300 K. It was shown that the current through the dielectric layer is controlled either by Pool-Frenkel mechanism of trap-assisted tunneling or by Mott's variable range hopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…44showed that there is no additional undesirable interfacial layer between Gdsilicate and silicon even for samples annealed up to 800°C. This is due to the small lattice mismatch as well as presence of Si atoms in Gd-silicate as mentioned which helped in preventing the IL formation[100].XPS of Si 2p peaks comparison for CeO 2 /TiO 2 and CeO 2 /GdSiO(Fig. 45) sample had further confirmed the presence of interfacial layer formation which matches well with our TEM and electrical data.…”
supporting
confidence: 84%
“…44showed that there is no additional undesirable interfacial layer between Gdsilicate and silicon even for samples annealed up to 800°C. This is due to the small lattice mismatch as well as presence of Si atoms in Gd-silicate as mentioned which helped in preventing the IL formation[100].XPS of Si 2p peaks comparison for CeO 2 /TiO 2 and CeO 2 /GdSiO(Fig. 45) sample had further confirmed the presence of interfacial layer formation which matches well with our TEM and electrical data.…”
supporting
confidence: 84%
“…Although pure HfO 2 tends to transform from amorphous to crystalline structure upon fabrication and/or post-fabrication processing [2,9], the formation of the tetragonal HfO 2 phase is the most preferable due to its higher k value (up to 70) and lower free energy in comparison with those of the monoclinic HfO 2 phase (k=16-18) [12,13]. It was also demonstrated that interface state densities can be reached as low as D it =(1.5-2.0)×10 11 eV -1 •cm -2 for Hf-based dielectrics grown on (100) Si substrate [1,14]. However, the formation of thick SiO 2 interfacial layer, separating the HfO 2 film from the Si substrate, is still an issue for HfO 2 applications [1,2,15].…”
Section: Introductionmentioning
confidence: 99%